2021
DOI: 10.1186/s12891-021-04030-0
|View full text |Cite
|
Sign up to set email alerts
|

Myostatin and markers of bone metabolism in dermatomyositis

Abstract: Background In dermatomyostis (DM) patients, inflammation, reduced activity, and medication have a negative impact on the musculoskeletal system. Several endocrine factors are involved in muscle growth and bone turnover. Objective: We aimed to investigate factors regulating myogenesis and bone metabolism and to evaluate possible associations between these endocrine factors, muscle strength, and functional tests in DM patients. Methods … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 41 publications
2
10
1
Order By: Relevance
“…Moreover, myostatin level was higher in inactive IIM patients compared to active ones, except for IMNM patients where it remained unchanged. Only a few studies have previously examined myostatin in IIM and they are often contradictory [13,14,[27][28][29][30]. Some results are concordant with our studies [13,14], whereas others are not [27][28][29][30],…”
Section: Discussionsupporting
confidence: 88%
“…Moreover, myostatin level was higher in inactive IIM patients compared to active ones, except for IMNM patients where it remained unchanged. Only a few studies have previously examined myostatin in IIM and they are often contradictory [13,14,[27][28][29][30]. Some results are concordant with our studies [13,14], whereas others are not [27][28][29][30],…”
Section: Discussionsupporting
confidence: 88%
“…There are only 2 studies analyzing serum levels of myostatin and follistatin in DM and PM, and these studies showed contradictory results. 22,33 Vernerova et al 22 evaluated serum levels of myostatin and follistatin in 94 IIM patients with short disease duration, 44 established rheumatoid arthritis (RA), 36 early RA patients without corticosteroids, and 134 healthy control subjects; the authors reported decreased serum myostatin levels and increased follistatin levels. The authors also evaluated muscle biopsies in 20 IIM patients and 28 healthy control subjects and found an increased follistatin gene expression in patients with IIM.…”
Section: Discussionmentioning
confidence: 99%
“…In dermatomyositis, an inflammatory condition, the plasma myostatin concentration is elevated [ 23 ]. Importantly, the same study also found higher FGF23 levels in patients with dermatomyositis [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…In dermatomyositis, an inflammatory condition, the plasma myostatin concentration is elevated [ 23 ]. Importantly, the same study also found higher FGF23 levels in patients with dermatomyositis [ 23 ]. Moreover, CKD, another disease associated with elevated FGF23 levels [ 26 ], is characterized by a higher myostatin plasma concentration [ 46 ] and enhanced myostatin expression in muscle of mice [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation